The Relationship of Emotional Intelligence–Based Supervision to the Quality of Nursing Care Services: A Cross Sectional Studies - Nur Mukarromah; Misutarno Misutarno (Indonesian Academia Health Sciences Journal, 2025)
The quality of nursing care services is influenced by managerial and interpersonal factors, including supervision practices. Emotional intelligence–based supervision is considered a relevant approach to support nurses in delivering effective and patient-oriented care. This study aimed to examine the relationship between emotional intelligence–based supervision and the quality of nursing care services. This study used a quantitative correlational design with a cross-sectional approachA total of 168 nurses were included using a cluster-based sampling approach by work unit. Data were collected using structured questionnaires that measured emotional intelligence–based supervision and the quality of nursing care services. Both variables were categorized into good, fair, and poor levels for analysis. Descriptive statistics were used to describe respondent characteristics and variable distributions. The relationship between variables was analyzed using cross-tabulation, Chi-square test, and correlation analysis. The results showed that most respondents who experienced good emotional intelligence–based supervision also demonstrated good quality of nursing care services. In contrast, respondents who reported poor supervision tended to have poorer service quality. Statistical analysis indicated a significant relationship between emotional intelligence–based supervision and the quality of nursing care services, with a moderate positive correlation. These findings suggest that better supervision characterized by empathy, emotional regulation, supportive communication, and constructive guidance is associated with better nursing care quality. In conclusion, emotional intelligence–based supervision plays an important role in improving the quality of nursing care services. Strengthening supervisors’ emotional intelligence competencies may support better nursing management and service outcomes.